1999
DOI: 10.4102/jsava.v70i3.769
|View full text |Cite
|
Sign up to set email alerts
|

The sedative and analgesic effects of detomidine-butorphanol and detomidine alone in donkeys

Abstract: Butorphanol and detomidine constitute an effective combination for sedation and analgesia in horses. This trial was undertaken to assess the effectiveness of this combination in donkeys. The detomidine and butorphanol were given intravenously one after the other. A dose of 10 mg/kg of detomidine and 25 mg/kg of butorphanol was used. Sedation is easily extended by additional doses of butorphanol. The average dose of detomidine was 11.24 mg/kg and that of butorphanol was 28.0 mg/kg. Four donkeys in the detomidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 12 publications
6
39
1
1
Order By: Relevance
“…Using similar mechanical nociceptive devices and rates of application of force, basal MNT values in this study were comparable to those from previous studies on donkeys (Lizarraga and Beths 2012, Lizarraga and Janovyak 2013, Lizarraga and Castillo-Alcala 2014). However, Grint and others (2014) reported mean MNT values of 9.2 N using a rate of application of force of 0.4 N/second in donkeys.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using similar mechanical nociceptive devices and rates of application of force, basal MNT values in this study were comparable to those from previous studies on donkeys (Lizarraga and Beths 2012, Lizarraga and Janovyak 2013, Lizarraga and Castillo-Alcala 2014). However, Grint and others (2014) reported mean MNT values of 9.2 N using a rate of application of force of 0.4 N/second in donkeys.…”
Section: Discussionsupporting
confidence: 88%
“…In the study reported here, detomidine induced dosage-dependent mechanical antinociception with 20 μg/kg, inducing larger MNT AUC values than 10 μg/kg. Dosage-dependent mechanical antinociception has also been reported for the α 2 -adrenoceptor agonists medetomidine and xylazine (Muge and others 1994, Lizarraga and Beths 2012). Together, this demonstrates that MNT testing is a technique capable of detecting changes in nociceptive thresholds after the administration of α 2 -adrenoceptor agonists and that these drugs induce dosage-dependent mechanical antinociception.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, in contrast to earlier reports that higher doses of α 2 -adrenoreceptor agonists are required in donkeys to achieve equipotent sedative and analgesic effects compared to horses (Matthews and others 1997b, Joubert and others 1999), xylazine was shown to produce a similar degree of mechanical hypoalgesia under the same conditions to that achieved in horses at the same dose (1.1mg/kg) (Lizaragga and Beths 2012).…”
contrasting
confidence: 64%
“…The MDM and its dextro-isomer (dexmedetomidine) (DXM) also has been previously used in similar studies (Bartram et al, 1994, Grimm et al, 2000, Ko et al, 2000, Leppanen et al, 2006, Salla et al, 2014, Puighibet et al, 2015, Lee et al, 2016, Tamura et al, 2016. The same combination in other animal species also proved to be efficient for sedation and antinociception like in equine (Joubert et al, 1999, Abu-Ahmed, 2007 and in ruminant (Carroll et al, 1998, Lin andRiddell, 2003). However, injection of BTR and NLF each alone have limited analgesic potency (Gunion et al, 2004), it's co-administration with sedatives considered perfect combination as they result in synergistic effect for both sedation and antinociception (Sullivan et al, 1987, Grimm et al, 2000, Lester et al, 2003.…”
Section: Resultsmentioning
confidence: 99%